Variant form of hairy cell leukemia. Issue 6 (6th May 2019) - Wiber, Margaux; Maitre, Elsa; Cornet, Edouard; Salaün, Véronique; Naguib, Dina; Troussard, Xavier
Abstract: Mature lymphoid B‐cell proliferations with hairy cells represent heterogeneous entities where specific diagnosis is difficult but important since it impacts therapeutic management. The clinical cases of variant hairy cell leukemia reported herein illustrate the persistence of a clear interest in the use of splenectomy as a therapeutic alternative. Furthermore, ibrutinib appears to be a promising treatment in patients with relapsed/refractory disease. Abstract : Mature lymphoid B‐cell proliferations with hairy cells represent heterogeneous entities where specific diagnosis is difficult but important since it impacts therapeutic management. The clinical cases of variant hairy cell leukemia reported herein illustrate the persistence of a clear interest in the use of splenectomy as a therapeutic alternative. Furthermore, ibrutinib appears to be a promising treatment in patients with relapsed/refractory disease.